Does reading fluency mediate the relationship between cognitive-linguistic skills and reading comprehension? A study in European Portuguese - Cadime, Irene Maria Dias (2024)
Research has consistently revealed the existence of an interconnection between reading comprehension, word reading, reading fluency, vocabulary and rapid naming. The main goal of this study was to explore the possible mediating role of reading fluency in the relationship between reading comprehension and the remaining skills, and to test whether the magnitude of these relationships was similar across different years of schooling. For this purpose, a longitudinal study with two assessment time points was carried out in a sample of 2nd and 3rd graders who were learning to read in European Portuguese, an intermediate-depth orthography. The results evidenced that reading fluency not only directly influences reading comprehension but also plays a mediating role in the relationship between reading comprehension and skills such as word reading and rapid naming. On other hand, the results indicate a unique effect of vocabulary on reading comprehension. Taken together, these results have important implications for educational practice, suggesting that explicit intervention in reading should include both the teaching and training in reading fluency and the construction of a richer lexical repertoire.